An Analytical Study of Buddhist Art and Jain Art - Rohit, Ramesh (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: Buddhist and Jain artworks are rich manifestations of spiritual and cultural meaning. Buddhist art includes portrayals of Gautama Buddha, Bodhisattvas, narrative scenes, mandalas, and Buddhist-related things such as stupas and temple architecture. Buddhist art originated in the northern Indian subcontinent and changed as Buddhism expanded throughout diverse regions, influencing and being inspired by local creative traditions. Objective: The objective of this paper is to explore both Buddhist and Jain artworks that have a lengthy history of creation and evolution, reaching back to the Maurya and Kushan eras highlighting the art forms that contain spiritual significance, serving as visual representations of Buddhist and Jain theories and beliefs. Methodology: Library-based historical and textual analysis approach as well as has been applied to carryout this research and visual analysis of the art work and architectural features have been used for data collection to study the evolution and significance of Buddhist and Jain artworks. Result: Buddhist art have been found evolved from early Buddha's sculptures to include Bodhisattvas reflecting Buddha's biography, His teachings and the Buddhist philosophy where as Jain art has been found marked by simplicity, serenity and beaty depicting Tirthankaras like Mahavira and Parshvanatha, reflecting Jain philosophy. Both art forms visually represent their respective beliefs and teachings and philosophy. Conclusion: Buddhist art and Jain art have a long history reaching back to Mouryan and Kusan dynasty. Buddhist art began with devotional sculptures of Buddha and events from his life, but gradually expanded to include depictions of Bodhisattvas and other figures as prominent subjects. Jain art, on the other hand, is distinguished by its simplicity, elegance, and emphasis on symmetry and proportion, reflecting Jain philosophy and values.